A nomogram to predict anal condyloma acuminatum recurrence in HIV-negative patients following photodynamic therapy: A decade-long retrospective clinical study at a single tertiary hospital - Shu Zhou; Zhiyi Xu; Li Gu; Xiaoyu Zhai; Jing Zhao; Liqun Gu; Bingrong Zhou; Hui Hua (Photodiagnosis and Photodynamic Therapy, 2024)
Background: Anal condyloma acuminatum (CA) is marked by its thorny treatment and high recurrence rate. Although 5-aminolevulinic acid photodynamic therapy (ALA-PDT) demonstrates significant efficacy and safety in treating anal CA, it does not completely prevent recurrence. This study aimed to develop and validate a nomogram model in predicting the risk of relapse in HIV-negative patients with anal CA following treatment with ALA-PDT. Methods: A retrospective analysis was conducted on patients diagnosed with anal CA who received combined CO2 laser vaporization and ALA-PDT between January 2013 and May 2023. Patients were divided into recurrence and non-recurrence groups. A nomogram was developed based on factors showing statistical significance in multivariable logistic regression analysis. The discriminative ability and clinical utility of the nomogram were assessed via ROC curves and decision curve analysis, with internal validation performed through bootstrap resampling. Results: Among the 176 patients included, 33 (18.75 %) experienced recurrence, while 143 did not. Independent predictors for recurrence included HPV types, history of anal intercourse, and the number of CO2 laser treatments received. Incorporating these predictors, the nomogram demonstrated a superior diagnostic performance (area under the curve = 0.881, 95 % CI: 0.818–0.935) and a significant net benefit in decision curve analysis. Conclusions: The nomogram accurately predicts the risk of recurrence in HIV-negative patients with anal CA following ALA-PDT. It offers a valuable tool for guiding preoperative clinical decision-making and establishing personalized treatment strategies to minimize the risk of relapse.